I. Position of Stations, Surface Elevation and Thickness of the Ice Sheet, and Snow Temperature at 10m Depth in the Mizuho Plateau-West Enderby Land Area, East Antarctica, 1969-1971 - シミズ, ヒロム; ナルセ, レンジ; オオモト, クニオ; ヨシムラ, アイイチロウ; SHIMIZU, Hiromu; NARUSE, Renji; OMOTO, Kunio; YOSHIMURA, Aiichiro (National Institute of Polar Research, 1972)
P(論文) departmental bulletin paper